(untitled) (Global Journal of Science Frontier Research, 2019)
The United States under the Starfish program blew up a hydrogen bomb with a TNT equivalent 1.4 Mt in space above the Pacific Ocean. This event put a lot of questions before the scientific community. During the explosion, an electrical impulse of very short duration and large amplitude was detected. Modern electrodynamics can not explain this phenomenon. The article attempts to explain this phenomenon on the basis of the concept of the scalar-vector potential developed by the author of the article. A comparison of the calculated data obtained on the basis of this concept and the experimental results obtained during the bomb explosion gave a good agreement.